Summary writing as cognition and communication: A process of mapping the territory. - Piu, Angela; Dodman, Martin; Timpano, Giuseppina (Graphos. Rivista internazionale di pedagogia e didattica della scrittura, 2022)
The summary is assuming an increasingly significant educational value within the promotion of learning processes. In this article we propose a reconsideration of summary writing through an analogy with Bateson’s ecology of mind, examined from the perspective of the evolution of human language as a communicative and cognitive tool and of its written form, which renders it permanent and enhances both intra- and inter-mental reflection. We then consider how the reading-writing process underlying the summary can foster the development of both linguistic and transversal competences and also open new directions for educational research.